The effect of various position of square hollow section on the strength of foamed concrete beam with processed spent bleaching earth as partial replacement of cement - Lim, Chi Khang (2018)
Concrete have the characteristic of high strength, well plasticity, high elasticity modulus and workability in the world. But production of cement will consumes around 12% to 15% of the total industrial energy, therefore it becomes the second largest CO2 contributor in the world. Spent Bleaching Earth (SBE) is a solid waste that originating from edible oil refinery process which can generates high quantities of waste due to refining process of crude edible oil. The main component of Spent Bleaching Earth is silicon dioxide which around 57% or more depending to the type. Also, it is a very fine powder. The objective of this study is to determine the maximum load of the flexural beam by using 4-point bending test, to determine the deflection of beams and also to determine the mode of failure of the flexural beam. In this study, three different position of hollow beam (150x 200x 1500mm) which produced with 1600kg/m³ foamed concrete with 30% PSBE and all the beams were subjected to water curing for 28 days. Also, all the beams will use to determine the maximum load, deflection and the mode of failure by 4-point bending test. Results exhibit that the ultimate load decreased as the depth of hollow position increased (the percentage of strength lost for each beam were 12.7%, 35.4% and 37.3% for Beam 2, Beam 3, and Beam 4 respectively). Also, the increases of the depth of hollow section (close to neutral axis), the deflection is increases. It means that the flexural strength of the samples depends on the distance to the neutral axis of the beams. The maximum load and flexural strength of the beams with square hollow section at the neutral axis were 3.937kN and 0.787N/mm² which was higher than other hollow beams. In conclusion, the beams with square hollow section located at the neutral axis is the best beams for the future work development because it achieved higher loading and deflection after the portion of materials used decreased. In recommendation, the maximum loading and deflection of the beams will increase by added the reinforcement and the workmanship should be standardized to ensure the uniformity of beam compaction.